Characterization of the junction leakage of Ti-capped Ni-silicided junctions - Lee, Pooi See (2013)
The junction leakage characteristics of Ti-capped nickel-silicided diodes are presented. Ti-capped Ni-silicided devices rapid thermal annealed (RTA) at 400 °C exhibit high sheet resistances and suffer from narrow line effect, which leads to the suspicion that the total phase transformation of NiSi has not yet been achieved. On the other hand, Ti-capped Ni-silicided devices at 500 °C with low sheet resistance have a reverse leakage current comparable to that of pure NiSi. The 120 Å Ni/100 Å Ti-silicided junction at 500 °C has a consistent saturation current compared to that of pure NiSi on the shallow STI intensive leakage structures. On the leakage characteristics, the forward current mechanism is diffusion-dominated, specifically the minority carrier diffusion in the neutral region of the heavily doped side. The shallow p+/n comb diode has both Schottky contact and diffusion behavior in the forward active region.